2023
DOI: 10.1007/s00170-023-11527-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotational speed and feed rate on microstructure and mechanical properties of 6061 aluminum alloy manufactured by additive friction stir deposition

Abstract: Additive friction stir deposition(AFSD) is attractive for its ability to create freeform and fully-dense structures without melting and solidi cation. Hence, additive friction stir deposition is an alternative to fusion-based additive manufacturing technology. In this study, the in uence of AFSD parameter (i.e. rotational speed and feed rate) on the mechanical properties and microstructure of 6061 aluminum alloy is investigated. The as-deposited 6061 aluminum alloy exhibits relatively homogeneous microstructur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Overall, the deposition morphology of the samples, as well as the presence of defects, were found. The samples would form rounded curved areas in both the deposition start and end regions, and the advancing side (AS) of the deposited layer would be smoother than the receding side (RS), which is in agreement with the results of the experiments of the previous articles [41,45]. Under different rotational speed conditions, the morphology of the deposited layer changes due to the rotational speed.…”
Section: Macrostructuresupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the deposition morphology of the samples, as well as the presence of defects, were found. The samples would form rounded curved areas in both the deposition start and end regions, and the advancing side (AS) of the deposited layer would be smoother than the receding side (RS), which is in agreement with the results of the experiments of the previous articles [41,45]. Under different rotational speed conditions, the morphology of the deposited layer changes due to the rotational speed.…”
Section: Macrostructuresupporting
confidence: 88%
“…They found that the material flowed strongly at 400 rpm, the grain refinement was evident, and the average grain size reached 6.0 ± 3.3 µm. Chen et al [41] investigated the effect of the rotational speed and traverse velocity in the AFSD of 6061 aluminium alloy bars with a diameter of 10 mm. They found that the grain size positively correlates with the feed rate and rotational speed.…”
Section: Introductionmentioning
confidence: 99%
“…Various aspects of the mechanical and microstructural properties of AFSD AA6061 parts have been studied in the literature. The relationship between process parameters (deposition tool's rotation and traverse speed and feed-rate) and the mechanical properties and the microstructure/nanostructure properties for AA6061 parts that are made using AFSD has been investigated in studies [17,[58][59][60]. Zhu et al employed neutron diffraction to investigate the distribution of residual stress across the thickness of an AA6061 part that was fabricated using AFSD [61].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, fine-grained microstructure can be obtained in the final product materials due to the severe deformation during AFSD [27]. Consequently, using AFSD, bonding between Al alloy and Al alloy [28][29][30], as well as bonding between Ti alloy and Ti alloy [31][32][33], was performed. However, there is no study reported on the bonding between these two dissimilar metals (Al and Ti alloys) via AFSD.…”
Section: Introductionmentioning
confidence: 99%